PENGELOLAAN MANAJEMEN RESIKO DI TENGAH PERUBAHAN MODEL BISNIS TELEKOMUNIKASI - Firman Fauzi (Sekolah Tinggi Teknik - PLN, 2016)
In the age of information technology data today, telecommunication operators are focusing businesses and services in the data service, which originally was the only service of this data as a value added service (VAS). Then the data service is growing rapidly becoming part of the core business of the operators present. In the era of information technology this data, the risk faced by operators is the need to share the